1996
DOI: 10.1039/ft9969202825
|View full text |Cite
|
Sign up to set email alerts
|

Free-radical frontal polymerization: self-propagating thermal reaction waves

Abstract: Frontal polymerization is a mode of converting monomer into polymer via a localized reaction zone that propagates. Such fronts can exist with free-radical polymerization or epoxy curing. The necessary conditions for the existence of the free-radical frontal polymerization regime are considered. The physicochemical properties of monomers are classified in connection with complications arising in the experiments, including low conversion, convection and bubbles. The density gradient in the reaction zone leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
308
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 237 publications
(315 citation statements)
references
References 39 publications
6
308
0
1
Order By: Relevance
“…The growth of urban sprawl is another near 2D growth phenomenon for which detailed land use records and satellite imaging provide information about the front structure and dynamics (42). From a material science standpoint, it would be interesting to pursue studies of frontal polymerization (43), the corrosion of metallic films (44), and polymer dissolution (45), fronts in thin films to determine whether our results apply broadly to these phenomena as well. The general finding that fluctuation effects tend to make these fronts increasingly incoherent in time (diffuse) can be expected to have a large impact on the interaction of these frontal patterns under conditions where species (or different types of ordering) are competing for supremacy.…”
Section: Implications Of Observationsmentioning
confidence: 99%
“…The growth of urban sprawl is another near 2D growth phenomenon for which detailed land use records and satellite imaging provide information about the front structure and dynamics (42). From a material science standpoint, it would be interesting to pursue studies of frontal polymerization (43), the corrosion of metallic films (44), and polymer dissolution (45), fronts in thin films to determine whether our results apply broadly to these phenomena as well. The general finding that fluctuation effects tend to make these fronts increasingly incoherent in time (diffuse) can be expected to have a large impact on the interaction of these frontal patterns under conditions where species (or different types of ordering) are competing for supremacy.…”
Section: Implications Of Observationsmentioning
confidence: 99%
“…The only striking evidence of chemically driven viscous fingering for miscible autocatalytic systems occurs in polymeric systems where the monomer solution and the polymer matrix can have quite strong differences in viscosity. 9 In miscible systems, chemical reactions are more prone to provide density differences that can drive buoyantly unstable situations as soon as a heavier fluid lies on top of a lighter one. Experimental evidence [10][11][12][13][14][15][16][17][18][19][20] and theoretical studies [20][21][22][23][24][25][26][27][28][29][30][31][32] on density driven instabilities have shown that the coupling between buoyancy driven flows and chemical reactions can strongly affect the properties of the fingering instability.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction front is created by an external energy source, such as heat or light, and propagates through the system via consumption of the monomeric species. The PBFB technique is distinct from the previously published methods of frontal polymerization (Chechilo et al, 1972;Chekanov & Pojman, 2000;Pojman et al, 1996) in that it is based on the perfusion of a photoinitiator resulting in localized initiation and subsequent formation of crosslinked PEGDA hydrogels with gradients of mechanical properties and of immobilized YRGDS. In PBFP, gradients are generated by the controlled delivery of eosin Y, a photoinitiator, to the base of the monomeric solution via a perfusion pump and a glass frit filter disk.…”
Section: Perfusion Based Frontal Polymerizationmentioning
confidence: 99%